Issues in Nigeria-Senegal Relations: 2013-2018 - Adeyemo, Oluwatosin; Ade-Ibijola, Aderemi Opeyemi (African Journal of Stability and Development (AJSD), 2019)
Relations between Nigeria and Senegal dates back to the 1960s when the two West African countries established formal diplomatic relations. Strategic cooperation between the two countries has been facilitated through the NigeriaSenegal Binational Commission, even though this has not produced desired results. The Nigeria-Senegal Binational Commission was conceived to manage relations between both countries. In this context, this paper examines the economic and political objectives underpinning relations between Nigeria and Senegal within the period 2013-2018. The paper identifies lack of proper coordination and implementation of the Binational Commission framework as the major factor inhibiting relations between Abuja and Dakar. The study adopted a qualitative research method which is descriptive and explanatory.